2015
DOI: 10.2139/ssrn.2655559
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Power of the Business and Bank Sentiment of Firms: A High-Dimensional Granger Causality Approach

Abstract: Abstract. We study the predictive power of industry-specific economic sentiment indicators for future macro-economic developments. In addition to the sentiment of firms towards their own business situation, we study their sentiment with respect to the banking sector -their main credit providers. The use of industry-specific sentiment indicators results in a high-dimensional forecasting problem. To identify the most predictive industries, we present a bootstrap Granger Causality test based on the Adaptive Lasso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The extent to which the economic sentiment index offers relevant, timely insights regarding economic conditions can be translated into a Granger causality framework. A (set of) time series is said to Granger‐cause another time series if the former has incremental predictive power for predicting the latter (Wilms, Gelper, & Croux, ). In this section, we discuss the Granger causality test results to confirm that our newly created index has causality and predictive power for key economic indicators.…”
Section: Resultsmentioning
confidence: 99%
“…The extent to which the economic sentiment index offers relevant, timely insights regarding economic conditions can be translated into a Granger causality framework. A (set of) time series is said to Granger‐cause another time series if the former has incremental predictive power for predicting the latter (Wilms, Gelper, & Croux, ). In this section, we discuss the Granger causality test results to confirm that our newly created index has causality and predictive power for key economic indicators.…”
Section: Resultsmentioning
confidence: 99%
“…Bruestle and Crain (2015) have showed that controlling for significant versus insignificant changes in consumer confidence improved the accuracy of household expenditure forecasting models. Wilms et al (2016) have suggested selecting survey indicators from the most predictive industries in order to improve the predictive capacity of survey data. Similarly, Dreger and Kholodilin (2013) have noted that better performing survey-based indicators should be built upon pre-selection methods and data-driven approaches to determine the weights.…”
Section: Sweden United Kingdommentioning
confidence: 99%
“…Accordingly, survey results provide important information about agents' economic expectations, allowing comparisons among different countries' business cycles. On the one hand, sectoral results of the surveys have been often used as partial indicators for the construction of more general aggregate economic indicators and for the estimation of macro magnitudes through their introduction in econometric models (Abberger, 2007;Bruestle and Crain, 2015;Graff, 2010;Hanson et al, 2005;Lehmann and Wohlrabe, 2017;Wilms et al, 2016). On the other hand, survey-based expectations have also been introduced into behavioural equations postulated by economic theory such as the Phillips curve and to evaluate the formation of expectations, as they provide a direct measure of expectations to test the rationality of agents (Altug and Çakmakli, 2016;Bovi, 2013;Jean-Baptiste, 2012;Lee, 1994;Miah et al, 2016;Paloviita, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome COD, variable selection, which distinguishes important variables from noisy ones, is a popular and powerful technique in the realm of forecasting (Alberto et al, 2010; Hrdle et al, 2009; Refenes & Zapranis, 1999; Zeng, 2017). It can be regarded as a simplification procedure that extracts valuable data information from data by selecting important variable with predictive power (Ballings & Van den Poel, 2015; Bertsimas & Copenhaver, 2014; Ma et al, 2016; Wilms et al, 2016). In recent decades, variable selection focuses on penalizing methods that consider a minimization problem consisting of loss function and regularization terms (Guyon & Elisseeff, 2003; Nataraja & Johnson, 2011).…”
Section: Introductionmentioning
confidence: 99%